Colonization of bacteria and diatoms on an artificial substrate in a marine lake (eastern Adriatic Sea, NE Mediterranean) - Car, Ana (Array, 2020)
The initial colonization of bacteria and diatoms on a immersed artificial substrate and the development of diatom assemblages in relation to physico-chemical parameters were investigated on a weekly basis at one station in the marine Lake Mrtvo More, South Croatia, from April to October 2016. According to TRIX trophic index, lake showed different trophic character: (i) oligotrophic (at the beginning and the end of the study), (ii) mesotrophic (the end of June to mid-July), (iii) eutrophic (the end of July to mid-September). Heterotrophic bacteria increased to peak abundances (69,268 cells cm–2) at the beginning of June when the diatoms abundances start to increase. The lake has high diatom species richness (285 diatom taxa within 72 genera), with the highest species diversity index in August. Among diatoms, adnate were the primary colonizers, particularly Cocconeis dirupta W.Gregory var. flexella (Janisch and Rabenhorst) Grunow and Cocconeis scutellum Ehrenberg var. scutellum, while motile taxa joined the fouling communities from July to September. This study showed close relationship between diatom species composition and changes of physico-chemical parameters, particularly the nutrient concentrations.